Аналіз термодинамічної ефективності холодильних циклів в залежності від визначальних теплофізичних властивостей робочих речовин - Тарасова, Вікторія Олександрівна; Кузнецов, Михайло Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Показано принципову можливість визначення термодинамічної ефективності циклів холодильних машин і теплових насосів за обмеженою кількістю даних про властивості робочих речовин. Проведено дослідження термодинамічної ефективності парокомпресійних одноступінчастих простих і регенеративних циклів холодильних машин на різних робочих речовинах, отримано узагальнені регресійні залежності. Запропоновано нове аналітичне рівняння для оцінки ефективності простого і регенеративного циклів на основі визначального модифікованого критерію Клаузіуса.

The goal of this research was to develop the methods used for the analysis of the thermodynamic efficiency of the ordinary single-stage and regenerative cooling cycles depending on the determinant thermal-&-physical properties of cooling agents. The thermodynamic efficiency of the steam–compressive single-stage ordinary and regenerative cycles of cooling machines operating on different cooling agents has been investigated. The dependence was established between the effectiveness value of the use of the regeneration for the cooling cycle and the modified Clausius criterion of the cooling agent. Generalized regressive dependences were obtained for the evaluation of the efficiency of the ordinary and regenerative cycles based on the determinant modified Clausius criterion and these give us an opportunity to establish the fields for the preferential use of the promising cooling agents for regenerative cycles and establish requirements to the properties of cooling agents during their choice. These contribute to the selection of the rational flowchart for the specified thermal and physical characteristics of the cooling agent and for the thermal behavior of the unit operation and form appropriate rational geometric characteristics for the heat exchangers and interconnecting piping. The suggested methods enable the determination of the expected characteristics of the unit and the boundary attainable values of its efficiency in the conditions of the limited information on the thermal-&-physical properties of new (by-way) cooling agents without waiting for the appearance of accurate state diagrams. Analytical equations used for the estimation of the cooling factor depending on the modified Clausius criterion allow us to perform the frontend project computations making use of only absolute values of evaporation and condensation temperatures. The effect of the steam depression, the dryness value and the efficiency factor of the regenerative heat exchanger on the cooling factor of the cycle has been studied. A practical value of the obtained data consists in the opportunity of the objective and operative estimation of the efficiency of the use of the cooling agent for the regenerative and steam compressing cycles of the cooling machine using no multiparameter optimization procedure.
Analyzing the thermodynamic efficiency of cooling cycles depending on the determinant thermal and physical properties of operating media
Keywords: холодильний коефіцієнт; регенеративний цикл; холодоагент; критерій Клаузіуса; cooling factor; regenerative cycle; cooling agent; Clausius criterion